2013
DOI: 10.1371/journal.pone.0077926
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cerenkov Luminescence Imaging by Dual Excitation of Er3+, Yb3+-Doped Rare-Earth Microparticles

Abstract: Cerenkov luminescence imaging (CLI) has been successfully utilized in various fields of preclinical studies; however, CLI is challenging due to its weak luminescent intensity and insufficient penetration capability. Here, we report the design and synthesis of a type of rare-earth microparticles (REMPs), which can be dually excited by Cerenkov luminescence (CL) resulting from the decay of radionuclides to enhance CLI in terms of intensity and penetration. Methods: Yb3+- and Er3+- codoped hexagonal NaYF4 hollow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 41 publications
1
32
0
4
Order By: Relevance
“…Nylon phantom was chosen because of its similar scattering properties as the tissues49. Schematic design of the setup used for UCNPs/Spacers/AuNRs imaging in tissue phantom with different thickness is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nylon phantom was chosen because of its similar scattering properties as the tissues49. Schematic design of the setup used for UCNPs/Spacers/AuNRs imaging in tissue phantom with different thickness is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it appeared that an appropriate strategy might consist in transferring a portion of CR towards the near-infrared window by Cherenkov Radiation Energy Transfer (CRET). We, and others have demonstrated the feasibility of using CR to activate various platforms such as quantum dots and other nanoparticles, lanthanides, and fluorophores14151617181920212223. We rationalized the concept on organic fluorophores and showed that a single population of fluorophore, such as fluorescein, rhodamine-101 or rhodamine-6G, undergoes fluorescence emission upon irradiation by CR (from 90 Y, 177 Lu, or 18 F)(Fig.…”
mentioning
confidence: 98%
“…Such a phenomenon, so-called the Vavilov-Cherenkov effect, is not only function of the energy of the emitted particle, but it also relies on the refractive index of the medium. CR is an optical radiation that quickly became of interest for medical imaging: Cherenkov Luminescence Imaging (CLI) is now used in preclinical4567891011121314151617181920212223 and clinical24252627 settings. Some radiopharmaceuticals used in nuclear imaging (PET/SPECT) or radioimmunotherapy (RIT) are active in CLI, provided that they emit energetic enough beta particles456789101112131415161718192021222324252627.…”
mentioning
confidence: 99%
“…These interactions involve not only visible photons from the Cerenkov mechanism in an aqueous solution of [ 18 F]-FDG but also gamma-ray photons such as the 511 keV photons from positron annihilation originating from 18 F or 140 keV photons from technetium-99m ( 99m Tc) 30 . The authors coined this technique radiopharmaceutical-excited fluorescence imaging (REFI), which operates via a similar mechanism as previous work with dual-excited, rare-earth microparticles 31 . Through excitation by both mechanisms, the depth of imaging in tissue phantoms (artificial tissue mediums that mimic the absorption and scattering of tissue) and in vivo was shown to be superior compared with only CL (Fig.…”
Section: Nanoparticles and CL In Life Sciencesmentioning
confidence: 99%